KONSTRUKSI MAKNA LOVE YOYSELF DAN MENTAL HEALTH AWARNESS BAGI ARMY (KELOMPOK PENGGEMAR BTS) TERHADAP LAGU DAN CAMPAIGN MILIK BTS - Attia Nabilla Yasmin; Rhae Ayu Fardani (Universitas Teuku Umar, 2020)
ABSTRACTLove yourself / self love is interpreted as a condition when we can accept and appreciate ourselves, accept the advantages and disadvantages. BTS is a Korean boy band that has garnered international success, and is one of the bands that diligently voiced campaigns for ARMY (BTS fans) about self love through an album titled Love Yourself. The purpose of this study was to study how the ARMY had the meaning of Love Yourself and Mental Health Awareness of BTS songs. The method in this study is a qualitative method that addresses descriptive phenomena. The theory used to support this research is Dialogue Theory by Carl Rogers. In this study, it is used to discuss communication interactions that are formed from the actions and interactions of ARMY fans in interpreting self-love from the Love Yourself album series by BTS.Keywords : Love Yourself, Self-Love, Mental Health Awareness, BTS, Konstruksi Makna, ARMY.